ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) DENGAN TANAMAN JELUTUNG (Dyera spp.) PADA TANAH BERPASIR DI PASIR PANJANG KOTA SINGKAWANG - Desti, Desti; Muin, Abdurrani; Suryantini, Rosa (Universitas Tanjungpura, 2020)
In order to preserve jelutung plants, the Regional Government of Singkawang City has planted 38 trees in the Pasir Panjang area of Singkawang City. The purpose of this study: (1) to study the association of jelutung plants (Dyera spp) on those planted in Pasir Panjang Singkawang, (2) to determine the number of spores and their correlation with tree diameter, (3) to determine the FMA genus contained in the rhizosphere, and (4) percentage of root colonization to determine the level of association of AMF with jelutung plants. The study was conducted by survey method for sampling soil and roots of jelutung plants. Data were collected and analyzed in the form of the average number of spores, genus AMF and the percentage of infections in the roots of jelutung plants. The results of the research that has been done can be concluded that jelutung plants (Dyera spp) that grow in sandy habitats in the Pasir Panjang area of Singkawang City are associated with arbuscular mycorrhizal fungi (FMA). The results of spore calculations found in jelutung rhizosphere in sandy soil habitats are quite abundant with amounts ranging from 436 1279,67/100g of soil. The results of correlation analysis with the coefficient of determination r2 = 0,0169 showed no close relationship between diameter size and the number of spores in the jelutung rhizosphere of sandy soils. From the results of spore calculations, the genus Glomus sp found in the jelutung (Dyera spp) rhizosphere was 874,33 / 100 g of soil (96,8%), while the genus Gigaspora sp was only 23,97 / 100 g of land (2,6%), and Scutellospora sp only 5,50 / 100 g of soil (0,6%). Based on the calculation of the percentage of infections that occur at the root, it turns out that jelutung plants are included as a high level association with the percentage of infections ranging from 8,7 - 100% or being in grade 5.Keywords: Arbuscular Mycorrhizal Fungi (AMF), Jelutung Plants, Number of Spores, Percentage of Root Infection.